Toward Positive Youth Development 2008
DOI: 10.1093/acprof:oso/9780195327892.003.0014
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic School Integration

Abstract: High-poverty schools are defined here as those with more than 50% of students eligible for free and reduced-price lunch. See RICHARD D. KAHLENBERG, ALL TOGETHER Now: CREATING MIDDLE-CLASS SCHOOLS THROUGH PUBLIC SCHOOL CHOICE 106-12 (2001). Students are eligible for subsidized lunches if their families make less than 185% of the poverty line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Although there are some successful examples (Kahlenberg 2002(Kahlenberg , 2006, most SBSAs have done little to reduce either socioeconomic or racial segregation (Flinspach et al 2003, Reardon et al 2006, Reardon & Rhodes 2011. The student assignment plans in place today, then, are much weaker than desegregation plans of the 1960s and 1970s that substantially integrated schools.…”
Section: Factors Shaping Trends In School Segregationmentioning
confidence: 99%
“…Although there are some successful examples (Kahlenberg 2002(Kahlenberg , 2006, most SBSAs have done little to reduce either socioeconomic or racial segregation (Flinspach et al 2003, Reardon et al 2006, Reardon & Rhodes 2011. The student assignment plans in place today, then, are much weaker than desegregation plans of the 1960s and 1970s that substantially integrated schools.…”
Section: Factors Shaping Trends In School Segregationmentioning
confidence: 99%
“…Beginning in the 1990s, some school districts began to shift school assignment policies from focusing on racial diversity to focusing on income diversity. Kahlenberg (2002, 2006) found that the number of students in districts with attendance policies that consider family SES when assigning students grew from 1999 to 2006, but Reardon and Rhodes (2011) note that such districts enrolled only about 3% of all public school students in the United States. Reardon and Rhodes also found no evidence that income segregation levels change after districts adopt SES-based choice plans, a finding they attribute to the voluntary nature and weak design of these plans.…”
Section: Residential Income Segregation and School Assignment Policiesmentioning
confidence: 99%
“…The district tries to accommodate parental preferences, but does so within bounds. Controlled choice plans were an extension of magnet school programs that attempted to encourage racial balance through voluntary transfers rather than mandatory busing, and most controlled choice plans still structure their limits on choice around race, but in more recent years there have been efforts to use controlled choice to foster socioeconomic integration (Kahlenberg, 2007). Because they feature demand side choice and often are presented in the language of markets, controlled public school choice has added to the general impression that public agencies are giving up ground to market forces as a way to allocate services in the contemporary era.…”
Section: Choice and Market Forcesmentioning
confidence: 99%